Subcutaneous Mastectomy In Persistent Pubertal Gynecomastia: A Case Report - Putu Agus Sukarna; Ida Ayu Dewi Dhyani; I Gde Komang Agung Tresna Rahayudi; Agus Arya Mahottama; Ni Made Indah Prasatiya Ningsih (Jurnal Ilmu Kedokteran dan Kesehatan, 2026)
Gynecomastia Is An Enlargement Of The Glandular Tissue Of The Breast In Men Due To Proliferation Of Ducts And Stroma, Usually Due To An Imbalance In The Estrogen/Androgen Ratio. It Can Be Caused By Physiological (Neonatal, Puberty, Aging), Medications, Endocrine Disorders, Systemic Diseases, And Hormone-Producing Tumors. A Structured Evaluation Is Essential To Rule Out Pathological Causes. A 19-Year-Old Male With Onset Of Gynecomastia At 15 Years Of Age (Initial Size Of A Corn Kernel, Then Progressed To The Size Of A Ping-Pong Ball). No Pain, Discharge, Or Trauma History. Patient Had An Older Sister With Leukemia. No History Of Medication, Steroid, Or Supplement Use. During Physical Examinations Were Found A Left Subareolar Mass, Firm, Painless, Without Axillary Adenopathy. Breast Ultrasound Observed Dense Glandular Pattern Without Suspicious Solid Mass. Subcutaneous Mastectomy Was Done, The Masses Appeared Solid, Grayish-White, And Rubbery. Fibrocollagenous Tissue And Fat With Several Epitheliosis Was Observed Under Microscope. Final Diagnosis Was Persistent Pubertal Gynecomastia (Idiopathic, Possibly Influenced By Hormonal/Genetic Factors). Adolescents With Persistent Gynecomastia Require A Multidisciplinary Approach: A Comprehensive History, Complete Physical Examination, And Imaging Studies, And Psychosocial Considerations. A Family History Of Blood Cancer Should Be Noted, But A Causal Relationship With Gynecomastia Is Indirect And Requires Further Evaluation If Systemic Findings Are Present.